Margaret Laurence: Critical Reflections - David Staines (Les Presses de l'Université d'Ottawa | University of Ottawa Press, 2001)
This book highlights the accomplishments of one of Canada's most acclaimed and beloved fiction writers, Margaret Laurence. The essays in this collection explore her body of work as well as her influence on young Canadian writers today.